Validation Spanish of the Post-Traumatic Stress Disorder Scale in the Postpartum - City BITS - Ayelén Acosta; Aquiles Pérez Delgado; Mercedes Lotufo; Angela Zayas; Sandro Giovanazzi (Interacciones)
Background: Postpartum post-traumatic stress disorder (PTSD) has a prevalence of 3-4% in women, rising to 15-19% in the presence of risks during pregnancy or childbirth, and reaching 39% in the case of neonatal death. Perinatal complications can trigger a real or perceived threat to maternal or neonatal life, which can evoke intense emotional reactions equivalent to a traumatic stressor according to PTSD criteria. Four symptom clusters have been identified: re-experiencing, avoidance, negative cognitions and mood, and hyperarousal symptoms. Despite its high comorbidity with depression and anxiety, postpartum PTSD remains underdiagnosed in maternal settings. The Postpartum Posttraumatic Stress Disorder Scale, originally developed in England, is in the process of translation and global validation. Objective: To validate the Spanish adaptation of the City Birth Trauma Scale. Methods: Quantitative, nonexperimental, cross-sectional, descriptive-correlational study in a sample of 677 Argentine women with children under 12 months of age. Results: Exploratory factor analysis revealed two dimensions that explained 49.56% of the total variance. Confirmatory factor analysis supported the two-factor structure. The scale showed high internal consistency (total α = .903), with α = .872 for 'birth-related symptoms' and α = .886 for 'general symptoms'. Construct validity of the City BiTS was demonstrated by moderate associations with the DASS-21 subscales and a negative correlation with the BIEPS-A. Conclusions: The Spanish adaptation of the City Birth Trauma Scale is confirmed as a reliable and valid instrument, consistent with original research findings and subsequent validations, articulating postpartum PTSD in two symptom categories: birth-related and general.